Fatigue Analysis of the Taut-Wire Mooring System Applied for Deep Waters - 黄维 刘海笑 单桂敏 胡存 (China ocean engineering, 2011)
Precisely predicting the fatigue life of taut-wire mooring systems has become an interesting and important problem for scientists and engineers since there are still difficulties in the inspection and maintenance of mooring lines in a rough sea environment especially in deep waters. In this paper, a comprehensive fatigue analysis is performed for a polyester taut-wire mooring system of an FPSO based on the time domain dynamic theory, rainflow cycle counting method and linear damage accumulation rule of Palmgren-Miner. Three influential factors in the fatigue analysis including the pre-tension, dynamic stiffness and T-N curve are investigated in detail. Two polyester T-N curves, one is from the DNV- 0S-E301 and the other is from the API-RP-2SM, are adopted in the calculation. The fatigue analysis of the mooting system after one-line failure is also carried out. The calculation results indicate that the fatigue life is significantly affected by the T-N curve. The fatigue life decreases with increasing pre-tension, and is largely reduced if taking into account the dynamic stiffness caused by cyclic loading. The analysis also proves that one-line failure has remarkable effects on the fatigue lives of other mooting lines. The present parametric and comparative study is believed to be meaningful to further understanding of the taut-wire mooting system for deepwater applications.